Peran Pengalaman Studi ke Luar Negeri dalam Membangun Kompetensi Global - Hana Panggabean (Jurnal Ilmiah Psikologi MIND SET, 2012)
International study has been increasingly attractive due to its personal, academic, and economic benefits. However, studies on international students focus predominantly on adjustment problems. This study aims at identifying benefits of international study for Indonesian, both in personal growth and global career development. Furthermore, this study explores global competencies for Indonesians. Fifteen Indonesian sojourners in China (N=7) and Singapore (N=8) with international education background are interviewed to explore their personal experiences, insights and ideas on their international exposures during their study years and onwards. The study applies grounded theory approach to analyze the data. Seven personal development benefits are revealed: independency, self-responsibility, positive thinking, self-confidence, foreign language mastery, intercultural sensitivity and communication, and global mindset. Four competitive advantages are derived: networking, strategic thinking, international business mindset, agility, and management modeling. The study identifies nine global competences for Indonesian, namely: foreign language skill, stepping out of the comfort zone, professional work ethics, open-mindedness, intercultural sensitivity, and technical excellence.